Presentation of the final document of the table of human dignity - Andina, Instituto de Pastoral (1999)
The work of our Human Dignity Roundtable began with the Human Dignity and Integrality of Rights workshop, during the IPA course held in October 1998. In it we had the support of Eduardo Cáceres Valdivia, who he was elected advisor to the board. There we discussed the theme, formulated the objectives, defined the participation criteria and determined responsibilities among the four vicariates of Solidarity of the South Andean in the following way: coordination: Sicuani vicariate, secretariat: Ayaviri vicariate, organization: Julio vicariate, and diffusion: Vicariate of Puno.